Efficacy of Programs Designed to Reduce the Incidence of Premarital Sexual Behavior Among Adolescents: A Systematic Review - Desy Ayu Wardani; Siti Khuzaimah Ahmad Sharoni; Endang Triyanto (Jurnal Keperawatan Indonesia, 2024)
The incidence of premarital sexual behavior worldwide is increasing despite the fact that it is known that it may cause health and psychological problems. Hence, interventions are needed to reduce the incidence of premarital sexual behavior. The aim of this study was to provide an overview of the reported interventions used to reduce the incidence of premarital sexual behavior in adolescents and identify the implications for nursing practice. A systematic review was conducted using The Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. The Scopus, Science Direct, Web of Science, and ProQuest databases were searched using the keywords "premarital sexual behavior” and “sexual,” and three researchers independently examined the resultant selected full-text articles. Articles published between 2020 and 2022 that described studies with a randomized controlled trial (RCT) design and that were published in English and had the full text available were included. The quality of each article was assessed using the Joanna Briggs Institute Critical Appraisal Checklist. Seven articles met the inclusion criteria and were subsequently analyzed. Our study showed that different types of interventions have been tested to variously enhance education, motivation, skills, and empowerment. The findings of our study have implications for nursing practice in terms of the creation of intervention-based programs and standard operating procedures for implementing programs designed to reduce the prevalence of premarital sexual behavior. Keywords: adolescent, incidence, randomized controlled trial, sexual behavior   Abstrak Program Efikasi yang Dirancang untuk Menurunkan Kejadian Perilaku Seksual Pranikah pada Remaja: Tinjauan Sistematis. Angka kejadian perilaku seksual pranikah di seluruh dunia semakin meningkat meskipun diketahui dapat menimbulkan permasalahan kesehatan dan psikologis. Oleh karena itu, diperlukan intervensi untuk mengurangi kejadian perilaku seksual pranikah. Tujuan dari penelitian ini adalah untuk memberikan gambaran tentang intervensi yang digunakan untuk mengurangi kejadian perilaku seksual pranikah pada remaja dan mengidentifikasi implikasinya terhadap praktik keperawatan. Tinjauan sistematis dilakukan dengan menggunakan pedoman PRISMA. Basis data Scopus, Science Direct, Web of Science, dan ProQuest dicari menggunakan kata kunci "perilaku seksual pranikah" dan "seksual", dan tiga peneliti secara independen memeriksa artikel teks lengkap pilihan yang dihasilkan. Artikel yang diterbitkan antara tahun 2020 dan 2022 yang menjelaskan penelitian dengan desain randomized controlled trial (RCT) dan diterbitkan dalam bahasa Inggris serta teks lengkapnya disertakan. Kualitas setiap artikel dinilai menggunakan Joanna Briggs Institute Critical Appraisal Checklist. Tujuh artikel memenuhi kriteria inklusi dan kemudian dianalisis. Penelitian kami menunjukkan bahwa berbagai jenis intervensi telah diuji untuk meningkatkan pendidikan, motivasi, keterampilan, dan pemberdayaan. Temuan penelitian kami memiliki implikasi terhadap praktik keperawatan dalam hal penciptaan program berbasis intervensi dan prosedur operasi standar untuk implementasi program yang dirancang untuk mengurangi prevalensi perilaku seksual pranikah. Kata Kunci: kejadian, perilaku seksual, remaja, uji coba terkontrol secara acak